Different responses to phenological stages: a role for nickel in growth and physiology of herbaceous cotton - Aguilar, Jailson Vieira [UNESP]; Ferreira, Tassia Caroline [UNESP]; Bomfim, Nayane Cristina Pires [UNESP]; Mendes, Thalita Fisher Santini [UNESP]; de Marcos Lapaz, Allan; Brambilla, Matheus Ribeiro [UNESP]; Coscione, Aline Renee; de Souza, Lucas Anjos; Junior, Enes Furlani [UNESP]; de Camargos, Liliane Santos [UNESP] (Springer Nature, 2023)
Nickel (Ni) is an essential metal, known more for its toxicity than its role as a fertilizer. The behavior of cotton cultivation with Ni in the soil has not yet been well studied, this species is important in agribusiness and can benefit from the use of Ni as a fertilizer, it can also be used in phytoremediation studies. The objective was to evaluate the cotton plant’s development and physiological behavior in increasing Ni concentrations in two phenological stages. Seeds were planted in pots filled with soil at doses of 0, 15, 30, 45, 60, 75 e 90 mg dm−3 of Ni as sulfate. In seedlings, growth variables and molecular groups were measured to monitor the use of seed reserves. In adult plants, gas exchange, growth, and Ni content were measured. In seedlings, growth decreased when the seedling germinated at the highest Ni concentration. The high protein content of seedlings at 90 mg dm−3 indicates a disturbance in the use of seed reserves. The amino acid pool and the decrease in soluble sugars at 60 e 75 mg dm−3 seem to be related to defense strategies against Ni excess. In adult plants, growth also decreased at 90 mg dm−3, indicating that damage to seedlings harmed the adult plant. The photosynthetic peak was recorded in the 45 mg dm−3 treatment, which decreases together with chlorophylls at 75 e 90 mg dm−3. The cotton plant was not tolerant to Ni but demonstrates that it may have strategies to deal with potentially toxic Ni in the tissue.
Keywords: Amino acids; Gas exchange; Heavy metal; Phytoremediation; Proteins; Tolerance